Creative Advertising Management Application Strategy on Television in Indonesia - Margareta Habibah; Haderiansyah; Andri Setiawan; Syahrial Shaddiq; H. M. Zainul (Jurnal Mantik, 2021)
There are six strategies and group them into three categories: functionally oriented, symbolically / experience oriented, and product category oriented. Functionalally oriented advertising appeals to consumers, the need for tangible / physical / concrete benefits. This oriented style is a Unique Selling Proposition. Experience-oriented advertising strategies are geared towards psychosocial needs. (There are: Brand Image Strategy, Resonance Strategy, and Emotional Strategy). Domination strategy categories (there are: Generic Strategy and Preemtive Strategy) do not need to use a certain type of attraction for consumers but are designed to achieve an advantage compared to competitors in the same product category. It is important to note that, the differences are sometimes very obvious, and the execution of a particular advertisement can simultaneously employ several strategies.